Effect of Stenotrophomonas maltophilia Treatment on Pulmonary Function in Pediatric Patients. (4th October 2017) - Cowley, Maren; Nicho, Ana; Hand, Elizabeth
Abstract: Background: Stenotrophomonas maltophili a, a bacteria with broad, inherent antimicrobial resistance, commonly colonizes the respiratory tract of mechanically ventilated patients. Studies in adults have failed to show a difference in outcomes for patients treated or untreated for S. maltophilia respiratory cultures. Outcomes data in children, however, are lacking. The purpose of this study was to determine whether S. maltophilia treatment improves the pulmonary function of pediatric patients. Methods: A retrospective review of pediatric patients with S. maltophilia respiratory cultures between August 1, 2006 and August 1, 2016 was conducted. The primary objective was to compare pulmonary function improvement between patients treated and untreated for S. maltophilia . Results: Seventy-two patients were identified, 27 treated (T) and 45 not treated (NT). Baseline characteristics were similar except more untreated patients were in the NICU ( P = 0.036) and premature ( P = 0.021). Trimethoprim-sulfamethoxazole (88.9%) and minocycline(11.1%) were the most commonly used antibiotics for S. maltophilia. Most patients had polymicrobial cultures and were treated with concomitant antimicrobials (T 85.2%; NT 84.4%; P = 0.933). There was no statistical difference in pulmonary function improvement represented by ventilation parameters (T 77.8%; NT 75.6%; P = 0.830), radiographic findings (T 27.3%; NT 24.3%; P = 0.801), physical exam (T 30.4%; NT 27.0%; P = 0.776), maximum temperature (T 25.9%; NT 20.9%; P = 0.628), or white blood cell count (T 60.0%; NT 44.7%; P = 0.236). Hyperkalemia led to the discontinuation of trimethoprim-sulfamethoxazole in one patient. Overall, four patients died during hospitalization (T 11.1%; NT 2.2%; P = 0.111). Conclusion: No statistical difference in improvement of pulmonary function in patients treated or not treated for a positive S. maltophilia respiratory culture was identified. Treatment directed at S. maltophilia in polymicrobial respiratory infection may not improve outcomes. Further research is needed to determine when treatment of S. maltophilia in pediatric patients results in improved outcomes. Disclosures: All authors: No reported disclosures.